Educational financing and lifetime earnings - Robert M. Sauer (Brown University, Department of Economics, 2002)
This paper formulates and estimates a dynamic: programming model of the optimal edueational financing dedsions and post-graduation career choices of law school graduates. The purpose of the paper is to measure the effect of short-term parental cash transfers, received during school, on in-school work and borrowing decisions and post-graduation lifetime outcomes. The estimated parameters of the model imply that parental cash transfers do not significantly influence post-graduation lifetime earnings but do significantly influence lifetime consumption. In addition, a simulated counterfactual loan forgiveness program indicates that educational debt has only a modest influence on postgraduation career choices .
Keywords: C15; I22; J24; J44; 330; In-school Work; Educational Debt; Scholastic Achievement; Lifetime Consumption; Bildungsfinanzierung; Karriereplanung; Privater Transfer; Lebenseinkommen; Rechtsberufe; USA